Quantitative Peptidomics of Mouse Brain After Infection With Cyst-Forming Toxoplasma gondii - Zhou, Chun-Xue; Gao, Min; Han, Bing; Cong, Hua; Zhu, Xing-Quan; Zhou, Huai-Yu (Frontiers in Immunology, 2021)
Toxoplasma gondii is an obligate intracellular parasite capable of establishing persistent infection within the host brain and inducing severe neuropathology. Peptides are important native molecules responsible for a wide range of biological functions within the central nervous system. However, peptidome profiling in host brain during T. gondii infection has never been investigated. Using a label-free pepdomics approach (LC-MS/MS), we identified a total of 2,735 endogenous peptides from acutely infected, chronically infected and control brain samples following T. gondii infection. Quantitative analysis revealed 478 and 344 significantly differentially expressed peptides (DEPs) in the acute and chronic infection stages, respectively. Functional analysis of DEPs by Gene Ontology suggested these DEPs mainly originated from cell part and took part in cellular process. We also identified 3 novel neuropeptides derived from the precursor protein cholecystokinin, and 1 novel neuropeptides from acyl-CoA-binding protein. These results demonstrated the usefulness of quantitative peptidomics in determining bioactive peptides and elucidating their functions in the regulation of behavior modification during T. gondii infection.